Konparasi Syarat Keabsahan “Sebab Yang Halal” Dalam Perjanjian Konvensional Dan Perjanjian Syariah - Lukman Santoso; Tri Wahyu Surya Lestari (AL-ISTINBATH : Jurnal Hukum Islam, 2017)
As social beings, social relations are fundamental and inseparable. Social interaction that has many differences requires the existence of a specific guidance or law adopted by the community. The law is for the sake of realizing a sense of security and assured in establishing community relations, as well as to realize a good social relationship, harmonious and without having to harm others. A specific form of guidance in society is the agreement. Indonesia has three sub-systems of law that are broadly divided into namely western law, customary law, and Islamic law. The procurement of agreements in order to increase security and certainty is already inevitable in the modern era, which is rapidly growing as it is today. Therefore, before entering into an agreement, it is necessary to comply with all conditions of the validity of the agreement in order for the agreement to become valid as a law so that the purpose of the agreement can be reached. One of the terms of the validity of the treaty that is "lawful cause" is an important thing to be studied deeply by the parties who make the contract because of the difference of the legal system in its environment (Indonesia) is mainly the conventional agreement system which is used as the standard of legislation in Indonesia and the system Islamic agreement or sharia that is used as the guidance of the majority of Indonesian people who are Muslims, so that there are no things that do not want inflicted in the future